2011
DOI: 10.1227/neu.0b013e31822a547b
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Management of Hypoglossal Schwannomas Over 3 Decades

Abstract: The extreme lateral infrajugular transcondylar-transtubercular exposure approach, which is a modification of the extreme lateral suboccipital approach, provides sufficient exposure for most intracranial dumbbell-shaped hypoglossal schwannomas. Hypoglossal nerve reconstruction using a sural nerve graft improves tongue atrophy and movement for patients with resected nerves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 77 publications
1
24
0
Order By: Relevance
“…Hypoglossal schwannomas seems to have a female predilection (2.5:1) and mean age at diagnosis was 46 years [10,16]. These figures are in accordance with our case.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hypoglossal schwannomas seems to have a female predilection (2.5:1) and mean age at diagnosis was 46 years [10,16]. These figures are in accordance with our case.…”
Section: Discussionsupporting
confidence: 92%
“…The first case was reported by Slaughter et al in 1949 [9]. In a review of the literature by Cavalcanti et al in 2011, only 36 peripheral extracranial hypoglossal schwannomas were reported [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differentiating CCJ JACs from "cystic" hypoglossal schwannomas is challenging. In a series of 44 surgically treated hypoglossal schwannomas, Nonaka et al 21 found clinical presentations similar to CCJ JACs, with a female predominance, mean patient age of 45.8 years, and symptoms including ipsilateral tongue atrophy (92%), headache (61%), and dysphagia (32%). Hypoglossal schwannomas can be characterized as intracranial (31.5%), extraand intracranial "dumbbell" (50%), or extracranial (18.5%), 22 with secondary hypoglossal canal enlargement reported in up to 83%.…”
Section: Improving Ccjdd Lesion Recognition and Differentiating Jacs mentioning
confidence: 98%
“…Hypoglossal schwannomas can be characterized as intracranial (31.5%), extraand intracranial "dumbbell" (50%), or extracranial (18.5%), 22 with secondary hypoglossal canal enlargement reported in up to 83%. 21 So-called cystic hypoglossal schwannomas are uncommon, with cystic foci most often developing within large tumors with necrosis or spontaneous intratumoral hemorrhage. 23,24 In a previous cystic hypoglossal schwannoma case report, preoperative MR imaging showed peripheral enhancement surrounding cystic regions, whereas the tumor solid component enhanced uniformly.…”
Section: Improving Ccjdd Lesion Recognition and Differentiating Jacs mentioning
confidence: 99%